Identity, security and democracy the wider social and ethical implications of automated systems for human identification - Mordini, E. (Emilio); Green, Manfred (NATO science for peace and security. Series E; Human and societal dynamics, 2009)
Many people think of personal identification as only part of the security/surveillance apparatus. This is likely to be an oversimplification, which largely misrepresents the reality. 'Personal identity' means two separate concepts, namely that an individual belongs to specific categories and also that this individual is distinguished by other persons and understood as one. In other words, there are two different aspects involved in personal recognition: distinguishing between individuals and distinguishing between sets of people. The latter is likely to be the real issue. Dictatorships of any kind and totalitarian regimes have always ruled by categorizing people and by creating different classes of subjects. When rules want their subjects to humiliate themselves or their fellows, they create categories of people or exploit existing categories. From social and political points of view this allows a process known as 'pseudospeciation' to be produced. Pseudospeciation is a process which turns social and cultural differences into biological diversities. It promotes cooperation within social groups, overpowering the selfish interests of individuals in favor of collective interests, yet it also inhibits cooperation between groups, and it fosters conflict and mistrust. This work is dedicated to the thorny and multifaceted relations between identity, security and democracy. Identity, Security and Democracy shows how full of nuances the process of human identification is. IOS Press is an international science, technical and medical publisher of high-quality books for academics, scientists, and professionals in all fields.